ARTISTIC AND COMPOSITIONAL CHARACTERISTICS OF UZBEK AND ENGLISH RIDDLES (Academia Science Repository, 2023)
In world folklore studies, special attention is paid to determining the process of emergence of genres of folk oral works created in order to develop children's artistic thinking and aesthetic taste, as well as the historical-poetic gradual development. Elucidation of the genesis, ethnopedagogical content, poetic composition, and performance features of folklore lyrical examples aimed at young children is of great importance in opening the foundations of ethno-folkloristics, in substantiating the history of the integration of folklore with such disciplines as pedagogy and ethnography. Nowadays, the principle of researching the poetic nature of children's folklore, the composition of images, motives, and artistic-aesthetic tasks in direct connection with the state of performance is gaining strength in world folklore studies. As a result, it was proved that the formation and gradual development of similar genres in children's folklore of the peoples of the world is a component of the historical-folkloric process.